Inhibition of histone deacetylases induces K+ channel remodeling and action potential prolongation in HL-1 atrial cardiomyocytes - Lugenbiel, Patrick; Govorov, Katharina; Rahm, Ann-Kathrin; Wieder, Teresa; Gramlich, Dominik; Syren, Pascal; Weiberg, Nadine; Seyler, Claudia; Katus, Hugo; Thomas, Dierk (Cellular physiology and biochemistry, 2018)
Background/Aims: Cardiac arrhythmias are triggered by environmental stimuli that may modulate expression of cardiac ion channels. Underlying epigenetic regulation of cardiac electrophysiology remains incompletely understood. Histone deacetylases (HDACs) control gene expression and cardiac integrity. We hypothesized that class I/II HDACs transcriptionally regulate ion channel expression and determine action potential duration (APD) in cardiac myocytes. Methods: Global class I/II HDAC inhibition was achieved by administration of trichostatin A (TSA). HDAC-mediated effects on K+ channel expression and electrophysiological function were evaluated in murine atrial cardiomyocytes (HL-1 cells) using real-time PCR, Western blot, and patch clamp analyses. Electrical tachypacing was employed to recapitulate arrhythmia-related effects on ion channel remodeling in the absence and presence of HDAC inhibition. Results: Global HDAC inhibition increased histone acetylation and prolonged APD90 in atrial cardiomyocytes compared to untreated control cells. Transcript levels of voltage-gated or inwardly rectifying K+ channels Kcnq1, Kcnj3 and Kcnj5 were significantly reduced, whereas Kcnk2, Kcnj2 and Kcnd3 mRNAs were upregulated. Ion channel remodeling was similarly observed at protein level. Short-term tachypacing did not induce significant transcriptional K+ channel remodeling. Conclusion: The present findings link class I/II HDAC activity to regulation of ion channel expression and action potential duration in atrial cardiomyocytes. Clinical implications for HDAC-based antiarrhythmic therapy and cardiac safety of HDAC inhibitors require further investigation.
Das Pluszeichen im Titel ist hochgestellt
Gesehen am 24.07.2019